Geological Map of Greenland 1:100000 Ivigtut 61 V. 1 syd, The orogenic and Cratogenic Geology of a precambrian Shield Area. - Berthelsen, Asger; Henriksen, Niels (Meddelelser om Grønland, 1975)
The Ivigtut region forms part of the Precambrian shield of Greenland. The region includes the northern boundary zone of the Ketilidian fold belt (1800 m.y.) of south Greenland, and in the foreland area to the north two pre-Ketilidian orogenies can be distinguished. The oldest orogeny (Senilian) is characterised by alpinolype structures and the high grade metamorphism and migmatisation of a sequence of gneisses and amphibolites. The younger orogeny (Maturian) influenced a post-Senilian supracrustal sequence and led to reactivation of the adjacent Senilian basement rocks; low- to medium-grade metamorphic conditions were reached in the northern-most part of the Ivigtut region. Swarms of basic dykes (Iggavik dykes) were emplaced under cratogenic conditions after the Maturian orogeny, but prior to the deposition of Ketilidian supracrustal rocks which rest unconformably on the pre-Ketilidian basement. The Ketilidian supracrustals are weakly deformed and metamorphosed in the north but towards the south both these and the underlying gneisses are increasingly affected by the Ketilidian deformation and plutonism, and the original unconformity between pre-Ketilidian gneisses and Ketilidian supracrustals is obliterated. This change is accompanied by an increase in metamorphic grade from low greenschist facies to amphibolite facies. A series of autochthonous to allochthonous Kelilidian granites occur in abundance in the southern part of the Ivigtut region. The cratogenic Gardar period in the Ivigtut region (> 1250 m.y.) encompasses formation of intrusive complexes, emplacement of numerous swarms of dykes of various composition and extensive faulting activity. Intrusion of Mesozoic basic dykes and sills reflects the latest pre-Quaternary events.